Short Communication Determination of Positional Isomers of Monoenoic Fatty Acids Separated From Seed Oils of Nicotiana tabacum L. and Nicotiana rustica - Waheed, Amran; Saleem, Muhammad; Mahmud, Shahid (Biological Sciences - PJSIR, 2008)
. The octadecenoic acid separated from the seed oils of Nicotiana tabacum L. and Nicotiana rustica by the application of argentation thin layer chromatography was oxidized by modified Von Rudloff’s technique. The liberated monofunctional and difunctional carboxylic acids were separated and identified by the application of thin layer chromato- graphy and gas chromatography. The positional isomers determined in both species were cis-9-octadecenoic acid and cis-11-octadecenoic acid.